Knowledge on Genitourinary Fistula among Nurses in a Tertiary Hos-pital of Eastern Nepal - KC, Heera; Pokharel, Nirmala; Shrestha, Mangala; Rai, Gayatri; Parajuli, Surya Bahadur (Journal of College of Medical Sciences-Nepal, 2019)
Background: Genitourinary fistula, occurs most commonly due to preventable obstetric causes in developing countries. Women with obstetric fistula are at risk of infection, neglected from family and bear psychological distress due to stigma and social isolation. They require supportive care through multidisciplinary approach. Nurses occupying the larger workforce among the health-personnel are the frontier to care them throughout their life. Their knowledge on obstetric fistula will help to manage patients effectively. The aim of this research was to assess the knowledge on genitourinary fistula among nurses working in maternity wards of B. P. Koirala Institute of Health Sciences, Nepal. Methods: AHospital based cross-sectional study was conducted from May 2018 to January 2019 using self-administered questionnaire among nurses working in antenatal, intranatal, postnatal and gynecology ward of B. P. Koirala Institute of Health Sciences, Nepal. Forty nurses were enrolled after having informed consent. Collected data were entered in Microsoft excel and analysed using SPSS. Results: Only 42.5 % nurses had adequate knowledge on genitourinary fistula. Majority of them (90%) had correct response on definition of genitourinary fistula. Almost 83% correctly responded vesicovaginal fistula is the most common type. About 37.5% stated obstetric causes are main causes of genitourinary fistula in developing countries. Only 20% correctly responded the possible sign and symptoms of genitourinary fistula. Adequate knowledge on prevention of obstetric fistula (35%), surgical repair (20%), pre-operative management (12.5%) and discharge advice (20%) was found. Conclusions: This study concludes that majority of nurses working at antenatal, intranatal, postnatal and gynecology wards of B. P. Koirala Institute of Health Sciences, Nepal had moderate knowledge on genitourinary fistula.